Emerging Concepts and Evidence in Telematics Novel Approaches or Treatments for Spasticity Management After Botulinum Injection - Bascuñana-Ambrós, Helena; Nadal-Castells, Mª Josep; Ramírez-Mirabal, Eliot; Beranuy-Rodriguez, Marta; Pintor-Ojeda, Alberto; Perrot-González, Jean-Claude (Frontiers in Rehabilitation Sciences, 2021)
There is a strong recommendation to use intramuscular botulinum toxin in patients with progressing or persistent troublesome focal spasticity affecting one or more joints and who have an identifiable therapeutic goal. After the botulinum toxin injection a stretch intervention enhances the results 0f botulin toxin injection, and therefore should be done by patients and/or caregivers after being train by a therapist. The adherence to this recommendation is still low once the patient is no longer followed by a therapist. The pandemic COVID-19 has increased the use of telemedicine with different approaches to treat patients, increasing the use of motivational app, with virtual reality software and real-life videos providing a gaming experience that increases adherence. There are programs with the physical therapist-guided synchronous telehealth exercise or software with sensors based technology that shows the range of motion and the strength of a particular joint muscles. These new approaches to the follow up of the patients seem to increase the adherence to exercise because the need to be “watched and controlled” is achieved.